A REVIEW OF MANAGEMENT AND PROJECT PLANNING IN CONSTRUCTION INDUSTRY - AJINKYA R. BHOSALE; ROHIT BHOSALE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The construction industries are continuously growing since the last decade with the globalization. Success of any construction industry is dependent on the quality and timely delivery of the construction projects. Before thinking to start any construction project, decision makers have to prepare a complete plan for successful completion of project. Project planning and proper management leads to the success of any construction industry. It was observed that, the construction projects mainly delayed due to inappropriate planning and bad management. While planning any project one need to consider various factors affecting success of project and has to forecast the future problems too. Construction project management mainly deals with, manpower, funds, material, authorization from the government authorities, legal permissions and better coordination. In this paper, authors have carried out and extensive review of the opinions presented by the researchers.